Abdominal Wall Endometriosis Following Cesarean Section: Report of a Case - Selçuk Erkılınç; Coşkun Ümit; Gamze Erkılınç; İrfan Özer; Ali İrfan Güzel; Melike Doğanay (Gynecology Obstetrics & Reproductive Medicine)
Endometriosis is the presence of functional endometrial tissue outside the uterus. Abdominal wall endometriosis is the one of the rarest site of extra pelvic endometriosis (AWE). We herein report the clinical characteristics of a 29 year’s old (G2P2) woman with abdominal wall endometriosis, 21 months after the last cesarean section. A total excision of the mass was performed and final histopathology of the mass was reported as endometriosis. We recommend taking into consideration this rare condition especially in women presenting painful mass near the scar with previous caesarean section.